2020
DOI: 10.3390/s20247284
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-Based Diagnostics of Radial Clearances and Bolts Loosening in the Bearing Supports of the Heavy-Duty Gearboxes

Abstract: The problem solved in this research is the diagnosis of the radial clearances in bearing supports and the loosening of fastening bolts due to their plastic elongation (creep) or weak tightening using vibration signals. This is an important issue for the maintenance of the heavy-duty gearboxes of powerful mining machines and rolling mills working in non-stationary regimes. Based on a comprehensive overview of bolted joint diagnostic methods, a solution to this problem based on a developed nonlinear dynamical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…Further research is associated with the utilisation of a designed FEM model for simulation of different kinds of failures of impellers disks and blades, to assess their influence on vibration signals registered on the shaft bearing supports by equipment monitoring systems, and to develop methods of its efficient diagnostics as shown in [55][56][57] for other minerals processing machines.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is associated with the utilisation of a designed FEM model for simulation of different kinds of failures of impellers disks and blades, to assess their influence on vibration signals registered on the shaft bearing supports by equipment monitoring systems, and to develop methods of its efficient diagnostics as shown in [55][56][57] for other minerals processing machines.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these elements of vibrators are subjected to high loads and cyclic fatigue. By the specification of the producer (SKF), bearings for the vibrating sieving screen have greater than normal clearances, which play the most important role in their durability [ 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…Initially looseness will manifest itself as Type A, next as B, then as C, and finally only the noise floor will remain in the spectrum. Krot et al (2020) and He et al (2014) also found that bolt loosening is best diagnosed by using system natural frequencies.…”
Section: Mechanical Loosenessmentioning
confidence: 96%